2019
DOI: 10.1111/cea.13486
|View full text |Cite
|
Sign up to set email alerts
|

Indoor dust acts as an adjuvant to promote sensitization to peanut through the airway

Abstract: Background There is growing evidence that environmental peanut exposure through non‐oral routes, including the skin and respiratory tract, can result in peanut sensitization. Environmental adjuvants in indoor dust can promote sensitization to inhaled antigens, but whether they contribute to peanut allergy development is unclear. Objective We investigated whether indoor dust promotes airway sensitization to peanut and peanut allergy development in mice. Methods Female and male C57BL/6J mice were exposed via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 76 publications
0
40
0
Order By: Relevance
“…108 Smeekens et al have demonstrated an adjuvant effect of house dust, which enhanced peanut sensitization and ensuing peanut allergy in mice. 109 A study by Ormstad et al demonstrated that indoor SPM, particularly those less than 2.5 μm in diameter, acts as an allergen carrier and adjuvant capable of modulating local lymph node inflammatory responses. 110 It was suggested that the fine particles (PM 2.5 fraction) were able to penetrate deeply into the airways, inducing epithelial irritability and increased sensitivity to environmental allergens, which subsequently affect respiratory health and induce the chronic airway inflammation characteristic of asthma.…”
Section: Immune Regulationmentioning
confidence: 99%
“…108 Smeekens et al have demonstrated an adjuvant effect of house dust, which enhanced peanut sensitization and ensuing peanut allergy in mice. 109 A study by Ormstad et al demonstrated that indoor SPM, particularly those less than 2.5 μm in diameter, acts as an allergen carrier and adjuvant capable of modulating local lymph node inflammatory responses. 110 It was suggested that the fine particles (PM 2.5 fraction) were able to penetrate deeply into the airways, inducing epithelial irritability and increased sensitivity to environmental allergens, which subsequently affect respiratory health and induce the chronic airway inflammation characteristic of asthma.…”
Section: Immune Regulationmentioning
confidence: 99%
“…Experimental analyses also suggest that inhalation of food allergens can promote food sensitization and reactions 85 , 86 . Dolence et al .…”
Section: Food Antigen Samplingmentioning
confidence: 99%
“…Interestingly, a recent study revealed that indoor dust may act as an adjuvant and play a role in the exacerbation of inhaled food allergen sensitization. Inhaled indoor dust was shown to stimulate airway epithelial innate cytokine production and maturation, and lung type-1 cDCs and co-exposure of indoor dust and food allergens such as peanut led to the development of peanut‐specific Th2 cell differentiation and the accumulation of Tfh cell peanut‐specific IgE production 85 .…”
Section: Food Antigen Samplingmentioning
confidence: 99%
“…Finally, Smeekens et al have looked at whether indoor dust promotes airway sensitization to peanut and peanut allergy development in mice, as they do for aeroallergens . In this model, inhalation of low levels of peanut only caused peanut allergy when combined with indoor dust (Figure ).…”
mentioning
confidence: 99%